MetabNet: An R Package for Metabolic Association Analysis of High-Resolution Metabolomics Data - Uppal, Karan; Soltow, Quinlyn A.; Promislow, Daniel E. L.; Wachtman, Lynn M.; Quyyumi, Arshed Ali; Jones, Dean P. (Frontiers in Bioengineering and Biotechnology, 2015)
Liquid-chromatography high-resolution mass spectrometry provides capability to measure >40,000 ions derived from metabolites in biologic samples. This presents challenges to confirm identities of known chemicals and delineate potential metabolic pathway associations of unidentified chemicals. We provide an R package for metabolic network analysis, MetabNet, to perform targeted metabolome-wide association study (MWAS) of specific metabolites to facilitate detection of their related metabolic pathways and network structures.